Mencegah Terbentuknya Dinasti Politik Melalui Pola Rekrutmen Partai Politik (Studi Kasus Pencalonan Kepala Daerah di Solo 2020) - Imroatun Nika (Universitas Islam Indonesia, 2021)
So far, there has been a tendency for political parties to nominate candidates based on the wishes of the party elite, not through a democratic mechanism by considering the capabilities and integrity of the candidates promoted by political parties. The objectives to be achieved in this study are first, to determine the potential for the formation of political dynasties in the pattern of political party recruitment for the process of nominating regional chief in Solo 2020. Second, to determine the ideal political party recruitment model in preventing the formation of political dynasties in Indonesia. This research is normative juridical with a statutory approach and a concept approach. The results of this study conclude that first, the improper political recruitment process is closely correlated with the practice of forming a political dynasty as happened in the process of nominating regional chief in Solo 2020. The tendency to form a political dynasty will also have an unhealthy impact on the democracy, because check control and the balances of government needed in a democratic country are weak. In addition, this kind of process will open up more opportunities for the re-establishment of a political oligarchy. Second, in the future, an ideal political recruitment model is needed, such as the application of the civil service reform model or the compartmentalization model with an open recruitment process.Key Words: Dynasty; party; politics; recruitmentAbstrakSelama ini terdapat kecenderungan pencalonan kandidat oleh partai politik berdasarkan keinginan elit partai, bukan melalui mekanisme yang demokratis dengan mempertimbangkan kemampuan dan integritas calon yang diusung oleh partai politik. Tujuan yang ingin dicapai dalam penelitian ini yaitu, pertama, untuk mengetahui potensi pembentukan dinasti politik dalam pola rekrutmen partai politik terhadap proses pencalonan kepala daerah di Solo 2020. Kedua, untuk mengetahui model rekrutmen partai politik yang ideal dalam mencegah terbentuknya dinasti politik di Indonesia. Penelitian ini bersifat yuridis normatif dengan pendekatan perundang-undangan dan pendekatan konsep. Hasil penelitian ini menyimpulkan bahwa, pertama, proses rekrutmen politik yang tidak baik berkorelasi erat dengan praktik pembentukan dinasti politik sebagaimana terjadi pada proses pencalonan kepala daerah di Solo 2020. Kecenderungan untuk membentuk dinasti politik juga akan membawa dampak yang tidak sehat bagi demokrasi, karena kontrol check and balances pemerintahan yang diperlukan dalam negara demokrasi menjadi lemah. Selain itu, proses semacam ini akan semakin membuka peluang untuk kembali terbentuknya oligarki politik. Kedua, ke depan, diperlukan sebuah model rekrutmen politik yang ideal, seperti penerapan model civil service reform atau model compartmentalization dengan proses rekrutmen yang terbuka.Kata Kunci: Politik; partai; dinasti; rekrutmen